Optimal shape design and performance investigation of helically coiled tube heat exchanger applying MO-SHERPA. (March 2022) - Wang, Guanghui; Liu, Aoke; Dbouk, Talib; Wang, Dingbiao; Peng, Xu; Ali, Asif
Highlights: The corrected thermodynamic model of the heat exchanger is proposed. The application of the Entransy Loss Theory in the helically coiled tube heat exchanger is proposed. Three modeling methods are proposed and selected. MO-SHERPA is used to carry out shape optimization. Abstract: In this paper, the corrected thermodynamic model of the heat exchanger is proposed, the application of the Entransy Loss Theory in the helically coiled tube heat exchanger is modified, three modeling methods are proposed and selected, Entransy Loss Number ( N gHE ) combining with Performance Evaluation Criteria ( PEC ) and Field Synergy Number ( Fc ) as the objective function, the numerical method verified by the experiment combined with MO-SHERPA is used to carry out the geometry optimization with 120, 000 sets of different cross-sections under the same heat exchange area. The results show that the proposed modeling method combined with MO-SHERPA can effectively avoid sharp phenomena in the structure, and which has obvious advantages in terms of optimized structure search and optimized structure search speed; Multi-objective optimization results in optimal solutions for different objectives, making the selection of optimization results more flexible under different working conditions; The comparative analysis of different heat exchangers under the same heat exchange area shows that the PEC of the tube side is increased by 22%, and the N gHE can be reduced by up to 66%; the PEC of the shell side is increased by 4% ∼ 20%.